Preparation method of NiP2 crystal

Through the oscillating heating curve and co-solvent method, the heating and cooling conditions were optimized, and large-size and high-quality NiP2 single crystals were successfully grown, solving the problem of insufficient size and purity in traditional methods and reducing growth costs.

CN119593053AActive Publication Date: 2025-03-11INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411755787.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The prior art is difficult to grow large-sized NiP2 single crystals, and traditional methods limit the size and purity of the crystals.

Method used

Using oscillation heating curve and cosolvent method, under vacuum sealing conditions, large-sized NiP2 single crystals were successfully grown by optimizing the heating method and cooling rate.

Benefits of technology

The preparation of NiP2 single crystals with high quality, few defects and high purity is achieved, overcoming the problems of small size and uncontrollable in traditional methods, and reducing growth costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593053A_ABST
    Figure CN119593053A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of NiP2 crystals, i.e., NiP2 single crystals with different sizes and shapes are successfully prepared by adopting oscillation type heating to control the nucleation number of the crystals and controlling the cooling rate at the same time. Belongs to the technical field of material science. The crystal growth method provided by the invention has the advantages of simple process, low cost and controllable crystal size and shape. The method not only solves the problem that the large-size NiP2 single crystal is difficult to grow, but also has great significance for the development of a traditional crystal growth technology and a semiconductor preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material science, and specifically relates to NiP 2 Method for preparing crystals. Background Art

[0002] NiP 2 Crystal is an important functional material with excellent electronic, thermal and mechanical properties. Therefore, it is widely used in semiconductors, catalysis, energy storage and other fields. In recent years, with the development of semiconductor technology, there is an urgent need to improve the comprehensive performance of crystals such as size, purity and mechanical properties. Therefore, a NiP 2 The crystal growth process and the method of controlling its crystal size and crystal defects are of great significance.

[0003] Single crystal materials have a highly ordered crystal structure and often exhibit excellent physical properties in electricity and optics. They are irreplaceable materials in many high-tech fields. Single crystal materials are also of great significance for condensed matter physics research, because their nearly ideal crystal structure avoids defects from interfering with research results, which is of great significance for revealing the intrinsic physical properties of materials.

[0004] At present, the main methods for growing crystals include the Czochralski method, the Bridgman method, and the floating zone melting method. These methods are suitable for high melting point materials, and crystal growth requires a certain degree of supercooling. Chemical vapor deposition and physical vapor deposition are suitable for the growth of thin films, and require that the constituent elements of the material have similar melting and boiling points, and that the elements are easy to volatilize. Since the melting and boiling points of Ni and P elements are very different, Ni has an extremely high melting point, while P has a very low boiling point, so the above methods are not suitable for NiP. 2 Single crystal growth. In the laboratory, NiP is grown by the traditional solvent method. 2 The maximum size of a single crystal does not exceed 1mm, so it is necessary to find a suitable large-size NiP 2 The single crystal growth method is used to meet the application needs in semiconductors, catalysis, energy storage and other fields. Summary of the invention

[0005] The present invention aims to solve the technical problem of large-size single crystal growth. To this end, the main purpose of the present invention is to provide a NiP 2 The crystal growth method is to prepare NiP 2 In the single crystal process, by optimizing the heating method and using an oscillating heating curve, large-sized NiP was successfully grown. 2 Single crystal is to solve the problem that traditional process is difficult to grow large size NiP 2 The technical difficulty of single crystals is to prepare NiP with few defects and high purity. 2 Single crystal.

[0006] The specific technical solutions are as follows:

[0007] A NiP 2 Crystal preparation method, based on NiP 2 Polycrystalline and tin are used as raw materials, and the solvent method is adopted. Under vacuum sealing conditions, the temperature is raised to the upper limit temperature, and then the temperature is shaken and cooled to obtain NiP. 2 Single crystal; the oscillation heating is: between 700 and 1100°C, set to 2 to 6 oscillation cycles, preferably 3 to 5 oscillation cycles, one oscillation cycle includes: starting from the upper limit temperature - cooling to the lower limit temperature - keeping warm - heating to the upper limit temperature - keeping warm.

[0008] Furthermore, after the temperature is raised to the upper limit temperature, the heat preservation time is 24 to 48 hours;

[0009] Furthermore, the oscillating heating has an upper limit temperature of 900-1080°C, a lower limit temperature of 700-800°C, a cooling rate of 90-150°C / h, a heating rate of 60-100°C / h, and a holding time of 0.5-1h at the upper and lower limit temperatures;

[0010] Furthermore, during the cooling process, the crystal growth is controlled by controlling the cooling rate: when the cooling rate is 1-4°C / h, the crystal shape is flake-like; when the cooling rate is 4-6°C / h, the crystal shape is block-like; when the cooling rate is 6-8°C / h, the crystal shape is needle-like.

[0011] Furthermore, NiP 2 The molar ratio of polycrystalline to tin is 1:6 to 1:26, preferably 1:16 to 1:18, and the purity of the tin is 99.9% to 99.999%.

[0012] Further, the method comprises the following steps:

[0013] (1) Take NiP 2 The polycrystal and tin are placed in a container, which is evacuated and sealed;

[0014] (2) Place the above container in a high temperature furnace, raise the temperature to the upper limit, and then heat it by shaking.

[0015] Then cool down.

[0016] Furthermore, the vacuum condition in step (1) is 10 -3 Pa~10 -4 Pa.

[0017] Furthermore, the cooling process described in step (2) is cooled to 400-600° C. After the cooling is completed, the product is centrifuged and washed; the centrifugal speed is 1000-5000 r / min, and the centrifugal time is 3-60 s; the washing method is washing with a dilute hydrochloric acid solution, the time is 0.5-24 h, and the mass concentration of the dilute hydrochloric acid is 5-15%.

[0018] NiP prepared according to the preparation method of the present invention 2 Crystal, the crystal structure is monoclinic structure, the space group is C2 / c, and the lattice parameters are α=γ=90°, β=119.5615(8)°.

[0019] Further, the preparation of NiP 2 NiP used in single crystal 2 The preparation process of polycrystalline is as follows: 2 The Ni and P single substances are weighed in a stoichiometric ratio, ground and cold pressed, and then placed in a quartz tube for vacuum sealing; the sealed quartz tube is placed in a high-temperature furnace for annealing; the purity of the single substance powder is 98.5-99.999%; during the cold pressing process, the pressure is 100-600 MPa, the pressure holding time is 5-30 minutes; the vacuum condition is 10 -3 ~10 -4 Pa; the annealing treatment temperature is 900-1080°C and the time is 12-50h.

[0020] Advantages of the present invention:

[0021] The present invention proposes a new type of single crystal growth technology, which innovates the traditional flux method crystal growth technology and proposes an oscillating heating curve to grow large-size NiP 2 Single crystal technology. By using tin as flux, using an oscillating heating curve and controlling the cooling rate, high-quality and large-size NiP can be prepared. 2 Single crystal.

[0022] The present invention has a great innovation in the crystal growth method, which not only overcomes the NiP 2 The disadvantages of small size and uncontrollable single crystal growth technology also greatly reduce the NiP 2 The cost of single crystal growth is of great significance for improving the growth technology of large-size crystals and even the development of semiconductor manufacturing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 For NiP 2 X-ray diffraction results of polycrystals;

[0024] Figure 2 Schematic diagram of the container for flux method crystal growth;

[0025] Figure 3 For NiP 2 Temperature variation curve during crystal preparation;

[0026] Figure 4 NiP synthesized with different ratios of flux 2 Crystals;

[0027] Figure 5 For NiP 2 X-ray diffraction results of single crystals;

[0028] Figure 6 For NiP 2 Process flow chart of crystal growth;

[0029] Figure 7 NiP grown by normal heating curve and oscillating heating curve 2 Crystal contrast;

[0030] Figure 8 NiP grown at different cooling rates 2 Crystals;

[0031] Fig. 9 NiP prepared for different oscillation periods 2 Crystal. DETAILED DESCRIPTION

[0032] The present invention is further explained below with reference to the accompanying drawings and specific embodiments.

[0033] Example 1

[0034] NiP 2 Polycrystalline synthesis.

[0035] (1) Nickel powder and red phosphorus powder were weighed using an analytical balance. The purity of nickel powder was 99.999%, the particle size was 250 mesh (i.e., passing through a 250 mesh sieve), and the mass was 0.2599 g; the purity of red phosphorus was 98.5%, the particle size was 100 mesh (i.e., passing through a 100 mesh sieve), and the mass was 0.2975 g. The weighed nickel powder and red phosphorus powder were placed in an agate mortar and mixed evenly for 30-60 minutes, specifically 40 minutes here.

[0036] (2) The mixture is placed in a Φ12.7 mm mold and pressed into a small disc at a pressure of 500 MPa for 10 minutes. The small disc is placed in a corundum crucible, and the crucible is placed in a quartz tube and sealed in a vacuum environment with a vacuum degree of 10 -4Pa. The sealed quartz tube is placed in a muffle furnace for sintering, heated to 1080°C at a rate of 100°C / h, and then kept at 1080°C for 24-48h, specifically 30h here, and then cooled to room temperature along with the furnace.

[0037] (3) Repeat the previous process, grind the sample sintered in the previous process in an agate mortar, and then press it into a small disc in a Φ12.7 mm mold at a pressure of 500 MPa for 10 minutes. Place the small disc in a corundum crucible, and place the crucible in a quartz tube, which is sealed in a vacuum environment with a vacuum degree of 10 -4 The sealed quartz tube is placed in a muffle furnace for sintering, heated to 1080°C at a rate of 100°C / h, and then kept at 1080°C for 24-48h, specifically 30h here, and then cooled to room temperature along with the furnace.

[0038] The above process step (3) was repeated twice. The last sintered sample was ground in an agate mortar for 1-3 hours, specifically 2 hours. The ground powder was passed through a 400-mesh sieve (the powder under the sieve was taken), and then the diffraction data of the powder sample was tested using a laboratory smartlab small X-ray diffractometer. The sieved NiP 2 The powder is spread all over the sample pool, flattened with a glass sheet, and the sample pool is mounted on the test bench. The test parameters are set as follows: test angle 10-90°, step length 0.01°, speed 1° / min. The diffraction data is analyzed and compared with the standard card in the crystallographic library. The results are as follows: Figure 1 As shown, the synthesized NiP 2 The polycrystalline powder is pure phase, and the lattice parameters are α=γ=90°, β=119.5615(8)°.

[0039] Example 2

[0040] NiP 2 Flux ratio control for crystal growth.

[0041] Weighing NiP with an analytical balance 2 Polycrystalline powder and tin granules, NiP 2The polycrystalline powder is synthesized by Example 1, the purity of the tin particles is 99.999%, and the particle size is 1-4 mm. The masses of the weighed NiP2 polycrystalline powder and tin particles are 1.4484g:8.5517g (molar ratio is 1:6), 0.7807g:9.2195g (molar ratio is 1:12), 0.5972g:9.4023g (molar ratio is 1:16), 0.5344g:9.4658g (molar ratio is 1:18), 0.4835g:9.5169g (molar ratio is 1:20), 0.3761g:9.6234g (molar ratio is 1:26), for a total of 6 groups of experiments. The weighed mixture is placed in a corundum crucible, and then placed in a quartz glass tube, which is sealed in a vacuum environment with a vacuum degree of 10 -4 Pa. Figure 2 As shown, place two corundum crucibles with their upper and lower ends facing each other, put the mixture in the lower corundum crucible, and stuff quartz wool in the upper corundum crucible. Meanwhile, stuff quartz wool at the bottom and top of the quartz tube. Heat the sealed quartz tube in a muffle furnace to 1080℃ at a rate of 100℃ / h, and keep it at 1080℃ for 24-48h, specifically 30h here. Perform temperature oscillation before crystal growth, such as Figure 3 The oscillating heating area shown in the figure controls the number of nuclei by oscillating heating. The specific method is as follows: start from 1080℃ and cool to 800℃ at a rate of 100℃ / h, keep warm for 30 minutes, then heat to 1080℃ at a rate of 100℃ / h, and keep warm for 30 minutes. The above process is one cycle. After the temperature oscillates for 4 cycles, it is cooled to 500℃ at a rate of 3.6℃ / h. Take out the quartz tube at 500℃ and place it in a centrifuge for centrifugation. The centrifuge speed is 3000r / min. When the speed reaches the rated speed, start timing and centrifuge for 10s. Pick out NiP 2 Crystals were soaked in 10% dilute hydrochloric acid for 3-6 hours, specifically 4 hours. They were then dried in a vacuum drying oven at 100°C for 1 hour. 2 NiP synthesized by polycrystalline powder and tin particles molar ratio 2 Crystal condition Figure 4As shown, the size, quality and shape of the single crystal are evaluated. When the ratio is 1:6, a large number of small crystals are aggregated into blocks, and there are a large number of grain boundaries in the crystals. Cleavage is required to obtain small single crystals, and the quality is poor; when the ratio is 1:12, the crystals are not aggregated, the crystal size is small, generally needle-shaped, and the quality is average; when the ratio is 1:16, the crystal size is large, the shape is regular, and the quality is good; when the ratio is 1:18, the crystal size is large, the shape is regular, and the quality is good; when the ratio is 1:20, the number of crystals is small, the size is small and thin, and the quality is average; when the ratio is 1:26, the number of crystals is small, and they are generally thin sheets with average quality. Therefore, the ratios of 1:16 and 1:18 are determined to be the optimal ratios. NiP was tested by the laboratory smartlab small X-ray diffractometer 2 Single crystal diffraction of the crystal, the results are as follows Figure 5 As shown, the single crystal diffraction peak is steep and the half-width is small, indicating that the quality of the single crystal is very good.

[0042] Example 3

[0043] Oscillating heating curve control NiP 2 Crystal growth.

[0044] NiP 2 The single crystal preparation process is as follows Figure 6 As shown, NiP was weighed in a molar ratio of 1:18 in Example 2. 2 Polycrystalline powder and tin granules mixture, weighing NiP 2 The polycrystalline powder is 0.5342 g, the tin particles are 9.4653 g, and they are placed in a corundum crucible, which is then sealed in a vacuum environment with a vacuum degree of 10 -4 Pa. Sealing method such as Figure 2 As shown, the same as Example 2. The sealed quartz tube is placed in a muffle furnace for heating, and the temperature is raised to 1000°C at a rate of 100°C / h, and kept at 1000°C for 24-48h. Specifically, it is 30h here. The temperature is oscillated before the crystal growth, such as Figure 3 The oscillating heating area shown in the figure controls the number of nuclei by oscillating heating. The specific method is as follows: start from 1000℃ and cool to 800℃ at a rate of 100℃ / h, keep warm for 30 minutes, then heat to 1000℃ at a rate of 100℃ / h, and keep warm for 30 minutes. The above process is one cycle, the temperature oscillation lasts for 4 cycles, and then cools to 500℃ at a rate of 3.6℃ / h. Take out the quartz tube at 500℃ and place it in a centrifuge for centrifugation. The centrifuge speed is 3000r / min. When the speed reaches the rated speed, start timing and centrifuge for 10s. Pick out NiP 2 The crystals were soaked in 10% dilute hydrochloric acid for 3-6 hours, specifically 4 hours, and then dried in a vacuum drying oven at 100°C for 1 hour.

[0045] Example 4

[0046] Weighing NiP 2 The polycrystalline powder weighs 0.5344 g, the tin particles weighs 9.4656 g, and the other preparation processes are the same as those in Example 3, except that after the oscillating heating, the cooling rate is 2° C. / h.

[0047] Example 5

[0048] Weighing NiP 2 The polycrystalline powder weighs 0.5343 g, the tin particles weighs 9.4657 g, and the other preparation processes are the same as those in Example 3, except that after the oscillating heating, the cooling rate is 4° C. / h.

[0049] Example 6

[0050] Weighing NiP 2 The polycrystalline powder weighs 0.5345 g, the tin particles weigh 9.4651 g, and the other preparation processes are the same as those in Example 3, except that after the oscillating heating, the cooling rate is 7° C. / h.

[0051] Comparative Example 1

[0052] NiP grown by normal heating curve 2 Crystal

[0053] Weighing NiP 2 The polycrystalline powder is 0.5342 g, the tin particles are 9.4653 g, and they are placed in a corundum crucible, which is then sealed in a vacuum environment with a vacuum degree of 10 -4 Pa. The vacuum sealing method is the same as that in Example 3. The sealed quartz tube is placed in a muffle furnace for heating. The temperature is raised to 1000°C at a rate of 100°C / h. The temperature is kept at 1000°C for 24-48 hours, specifically 30 hours here. Then the temperature is cooled to 500°C at a rate of 3.6°C / h. The quartz tube is taken out at 500°C and placed in a centrifuge for centrifugation. The centrifuge speed is 3000r / min. When the speed reaches the rated speed, the timing is started and the centrifugation is continued for 10s. Pick out NiP 2 The crystals were soaked in 10% dilute hydrochloric acid for 3-6 hours, specifically 4 hours, and then dried in a vacuum drying oven at 100°C for 1 hour.

[0054] Figure 7 The crystals grown in Example 3 and Comparative Example 1 are shown, namely, the crystals grown by the common heating method and the oscillating heating method. The common heating method is to cool directly from high temperature, which makes it difficult to control the number of nuclei, resulting in a large number of crystal nuclei growing up. During the crystal growth process, it is easy to contact each other, thus limiting the crystal growth. The oscillating heating method in Example 3 is to heat NiP 2Oscillation is performed in the nucleation temperature zone. Although a large number of crystal nuclei are generated during the cooling process, the crystal nuclei will melt during the oscillation process. Only a few crystal nuclei that do not have time to melt are retained and continue to grow in the final cooling process. The advantage of the oscillation heating method is that the number of nuclei can be controlled. A small number of crystal nuclei grow during the cooling process, avoiding contact between crystals and limiting growth. Therefore, the crystals have more growth directions and can grow crystals with higher surface quality and larger crystal size. Figure 7 The size of crystals grown by the medium oscillation heating curve can reach 6mm×7mm×1mm.

[0055] Figure 8 Shown are NiP grown at different cooling rates in Examples 4-6 2 The crystal shape and size are 20mm×13mm×0.3mm when the cooling rate is 2℃ / h, 2mm×3mm×1mm when the cooling rate is 4℃ / h, and 1mm×1mm×10mm when the cooling rate is 7℃ / h. The oscillating heating curve allows a small amount of crystal nuclei to be retained, reducing contact during crystal growth and reducing crystal growth resistance. Therefore, the growth rate of the crystal can be controlled by controlling the cooling rate. The crystal grows along the direction of the temperature gradient with a preferential trend. The shape and size of the crystal can be controlled by controlling the cooling rate. The crystal growth rate can be controlled by controlling the cooling rate. When the cooling rate is small, 1°C / h~4°C / h, the crystal grows slowly and the preferential growth trend is weak, which is conducive to the growth of lamellar crystals with larger areas. When the cooling rate is fast, 6°C / h~8°C / h, the crystal grows faster and the preferential growth trend is obvious, which is conducive to the growth of thinner needle-shaped single crystals. When the cooling rate is moderate, 4°C / h~6°C / h, the crystal grows isotropically, which is conducive to the growth of thicker block single crystals.

[0056] Comparative Example 2

[0057] The specific preparation process is the same as that of Example 3, except that different oscillation heating cycles are set, namely 1, 2, 3, 5, 6, and 7 cycles.

[0058] The crystals prepared were Fig. 9As shown, the crystals grown in one oscillation cycle are small in size and large in number, indicating that one oscillation cycle is too short and the change in the number of nuclei is not obvious; the number of crystals grown in two oscillation cycles is significantly reduced, and the crystal size becomes larger, indicating that two oscillation cycles help to reduce the number of nuclei; the number of crystals grown in three oscillation cycles is further reduced, and the crystal size is larger than that of crystals grown in two oscillation cycles; the number of crystals grown in five and six oscillation cycles is basically the same as that of crystals grown in four oscillation cycles, indicating that the number of crystals grown in four oscillation cycles has reached a balance and the crystal size is the largest; continuing to increase the oscillation cycle has no obvious improvement on crystal growth, which may be applicable to other growth conditions; in the crystal preparation experiment with seven oscillation cycles, the quartz tube broke due to thermal fatigue, the vacuum environment was destroyed, and crystal growth could not proceed.

[0059] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a NiP2 crystal, characterized in that: NiP2 polycrystal and tin are used as raw materials, a solvent co-solvent method is adopted, and under vacuum sealing conditions, the temperature is raised to the upper limit temperature, and then oscillation heating is adopted, and then cooling is performed to obtain NiP2 single crystal; the oscillation heating is: between 700 and 1100°C, set to 2 to 6 oscillation cycles, preferably 3 to 5 oscillation cycles, and one oscillation cycle includes: starting from the upper limit temperature - cooling to the lower limit temperature - keeping warm - heating to the upper limit temperature - keeping warm.

2. The method according to claim 1, characterized in that: After the temperature is raised to the upper limit temperature, the insulation time is 24 to 48 hours; the oscillation heating: the upper limit temperature is 900 to 1080°C, the lower limit temperature is 700 to 800°C, the cooling rate is 90 to 150°C / h, the heating rate is 60 to 100°C / h, and the insulation time at the upper and lower limit temperatures is 0.5 to 1h.

3. The method according to claim 1, characterized in that: In the cooling process, the crystal growth is controlled by controlling the cooling rate: when the cooling rate is 1-4°C / h, the crystal shape is flake-shaped; when the cooling rate is 4-6°C / h, the crystal shape is block-shaped; when the cooling rate is 6-8°C / h, the crystal shape is needle-shaped.

4. The method according to claim 1, characterized in that: The molar ratio of NiP2 polycrystal to tin is 1:6 to 1:26, preferably 1:16 to 1:18, and the purity of the tin is 99.9% to 99.999%.

5. The method according to claims 1-4, characterized in that: The following steps are involved: (1) Put NiP2 polycrystal and tin in a container, evacuate and seal; (2) The container is placed in a high temperature furnace, heated to the upper limit temperature, heated by shaking, and then cooled.

6. The method according to claim 5, characterized in that: The vacuum condition in step (1) is 10 -3 Pa~10 -4 Pa.

7. The method according to claim 5, characterized in that: The cooling process described in step (2) is cooled to 400-600° C. After the cooling is completed, the product is centrifuged and washed; the centrifugal speed is 1000-5000 r / min, and the centrifugal time is 3-60 s; the washing method is washing with a dilute hydrochloric acid solution, the time is 0.5-24 h, and the mass concentration of the dilute hydrochloric acid is 5-15%.

8. The method according to any one of claims 1 to 7, characterized in that: The NiP2 crystal has a monoclinic structure, a space group of C2 / c, and a lattice parameter of α=γ=90°, β=119.5615(8)°.

9. The method according to any one of claims 1 to 7, characterized in that: The preparation process of NiP2 polycrystal is as follows: weigh Ni and P elements according to the stoichiometric ratio of NiP2, grind and cold press, and place them in a quartz tube for vacuum sealing; place the sealed quartz tube in a high-temperature furnace for annealing; the purity of the element powder is 98.5-99.999%; during the cold pressing process, the pressure is 100-600 MPa, the pressure holding time is 5-30 minutes; the vacuum condition is 10 -3 ~10 -4 Pa; the annealing treatment temperature is 900-1080°C and the time is 12-50h.

Citation Information

Patent Citations

  • Method of preparing barium yttrium borate and barium yttrium borate crystal and use thereof

    CN101054724A

  • Preparation method of centimeter-level pure-phase BiFeO3 monocrystal

    CN102953116A

  • Preparation method of anisotropic large-size crystal and AgCrSe2

    CN113564714A

  • NiP2-NiSe / g-C3N4 photocatalyst as well as preparation method and application thereof

    CN116212923A